2019
DOI: 10.1002/fsn3.1122
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and microbiological characteristics of kitoza, a traditional salted/dried/smoked meat product of Madagascar

Abstract: Kitoza samples collected from producers in Madagascar were analyzed for their physicochemical and microbial properties. Lactic acid bacteria and coagulase‐negative staphylococci were the two codominant populations with average counts of 6–7 log cfu/g. Good hygienic practices were sometimes lacking but samples were not contaminated with Salmonella , Clostridium perfringens , and Bacillus cereus and only once with Listeria monocytog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…in pH values (5.9-6.0). [23] Reported that pH of beef kitoza ranged from 5.26 to 6.22) similar to the pH of salted/dried beef products such as pastirma (5.7-6.1.) The acid value is the number of milligrams of sodium (or potassium) hydroxide necessary to neutralize the free acids in 1 gram of sample.…”
Section: Effect Of Different Processing Conditions On Microbial Populationsmentioning
confidence: 90%
“…in pH values (5.9-6.0). [23] Reported that pH of beef kitoza ranged from 5.26 to 6.22) similar to the pH of salted/dried beef products such as pastirma (5.7-6.1.) The acid value is the number of milligrams of sodium (or potassium) hydroxide necessary to neutralize the free acids in 1 gram of sample.…”
Section: Effect Of Different Processing Conditions On Microbial Populationsmentioning
confidence: 90%
“…These observations are highly associated with the water and salt content as well as the pH value of the dried meat. Many studies have been performed to evaluate the microbiological characteristics of the dried meat prepared in various preparation conditions, which includes microorganism like Staphylococcus aureus , Salmonella spp., Bacillus cereus and many others ( 74 , 87 ).…”
Section: Microbiological Characteristics Of Dried Meatmentioning
confidence: 99%
“…The traditional meat product of Malagasy or the Kitoza is a sun-dried and smoked meat strip that is important in the native diet. A study has investigated the microbial properties of the Kitoza samples obtained from various local productions in Madagascar ( 87 ). It was found that, in most of the samples, the two most dominant populations are the LAB and coagulase-negative staphylococci, with average microbial count ranging from 6 to 7 log cfu/g.…”
Section: Microbiological Characteristics Of Dried Meatmentioning
confidence: 99%
“…Calcium is an important mineral in human nutrition, being important for bone density. Calcium salts provide rigidity to the skeleton and calcium ions play many roles in most metabolic processes (Ratsimba et al, 2019). Nearly 99.0% of the Ca in the human body is found in the bones (Lorenzo et al, 2008).…”
Section: Mineral Content Of Kilishi Samplesmentioning
confidence: 99%